2017
DOI: 10.3389/fpls.2017.00934
|View full text |Cite
|
Sign up to set email alerts
|

Elicitor-Induced Biochemical and Molecular Manifestations to Improve Drought Tolerance in Rice (Oryza sativa L.) through Seed-Priming

Abstract: Rice (Oryza sativa L.) is one of the major grain cereals of the Indian subcontinent which face water-deficit stress for their cultivation. Seed-priming has been reported to be a useful approach to complement stress responses in plants. In the present study, seed-priming with hormonal or chemical elicitor [viz. methyl jasmonate (MJ), salicylic acid (SA), paclobutrazol (PB)] showed significant increase in total phenolic content, antioxidant activity and expression of Rice Drought-responsive (RD1 and RD2) genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 59 publications
5
47
0
Order By: Relevance
“…Insights into the molecular conservation of stress memory in crop species are scarce. However, like chemical priming of seeds to enhance stress tolerance of young plants, referred to as seed-priming [115], understanding the mechanisms of stress priming/memory might enable manipulation for tailored responses of crop plants to respond more efficiently to the challenges presented by the climate change. Thus, there is great potential for generation of environment-mediated heritable epigenetic variations, which actually drive/influence the evolution process in living organisms.…”
Section: Future Perspectives Of Epigenomic Studiesmentioning
confidence: 99%
“…Insights into the molecular conservation of stress memory in crop species are scarce. However, like chemical priming of seeds to enhance stress tolerance of young plants, referred to as seed-priming [115], understanding the mechanisms of stress priming/memory might enable manipulation for tailored responses of crop plants to respond more efficiently to the challenges presented by the climate change. Thus, there is great potential for generation of environment-mediated heritable epigenetic variations, which actually drive/influence the evolution process in living organisms.…”
Section: Future Perspectives Of Epigenomic Studiesmentioning
confidence: 99%
“…Also, seedpriming with selenium (Se) and SA was found to be effective in protecting rice plants against chilling stress [8]. Recently, bio-elicitorinduced biochemical and molecular manifestations to improve drought tolerance in rice [9] and impact of seed priming on proline content and antioxidant enzymes to mitigate drought stress in rice have been already reported [10].…”
Section: Journal Of Plant Biochemistry and Physiologymentioning
confidence: 99%
“…Mutant lines indicated tolerance to drought in a selection processes, it should be showing relationship between phenotype and genotype. Based on reports from QTL and molecular data showed that a key gene has immediate response to drought and other biotic stressed Samota et al, 2017;Borah et al, 2017;Prince et al, 2015). The plant's phenotype showed tolerance to drought can be observed such as panicle length and fertile grains, roots length.…”
Section: Introductionmentioning
confidence: 99%